2021
DOI: 10.1159/000520371
|View full text |Cite
|
Sign up to set email alerts
|

Primate Selfies and Anthropozoonotic Diseases: Lack of Rule Compliance and Poor Risk Perception Threatens Orangutans

Abstract: Our understanding of the transmission of anthropozoonotic diseases between humans and nonhuman primates, particularly great apes due to their close genetic relationship with humans, highlights a serious potential threat to the survival of these species. This is particularly the case at tourism sites where risk of disease transmission is increased. We focus on the interaction between tourists and the Critically Endangered Sumatran orangutan (Pongo abelii) at Bukit Lawang in the Gunung Leuser National Park, Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Other studies arbitrarily grouped information into monthly periods. For instance, Molyneaux et al (2021) compared the monthly number of photographs posted on Instagram before and after the onset of the COVID-19 pandemic to quantify variation in interactions between tourists and orangutans. Barros et al (2019) observed that Flickr geotagged data have enough information to capture daily, weekly and monthly distribution patterns of visitors of Spanish national parks, but did not perform temporal comparisons of visitor numbers across years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies arbitrarily grouped information into monthly periods. For instance, Molyneaux et al (2021) compared the monthly number of photographs posted on Instagram before and after the onset of the COVID-19 pandemic to quantify variation in interactions between tourists and orangutans. Barros et al (2019) observed that Flickr geotagged data have enough information to capture daily, weekly and monthly distribution patterns of visitors of Spanish national parks, but did not perform temporal comparisons of visitor numbers across years.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies arbitrarily grouped information into monthly periods. For instance, Molyneaux et al . (2021) compared the monthly number of photographs posted on Instagram before and after the onset of the COVID-19 pandemic to quantify variation in interactions between tourists and orangutans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations